Linguistic features of historical epics - Rakhimbayeva Г.К. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2020)
One of the largest genres of Kazakh folklore, the epic genre often uses borrowed words, obsolete words, and various language elements. They can accurately reflect the life of a particular era, the worldview of the time, the mind, and national identity.The article analyzes the nature of the use of Arabic, Persian, Uzbek and Russian words, which are often found in some versions of historical epics, including the epics «Barak Batyr, Abylay», «Bazar Batyr», «Myrzash Batyr», « Tobagul Batyr” and is substantiated using specific examples. The meanings of difficultto-understand Arabic, Persian borrowings or dialectics, dialect, archaism, elements of spoken speech are given and the purpose of their use is determined